Towards Dielectric Chip-to-Chip Interconnects for THz Applications - Bader, Tobias; Gold, Gerald (2024 IEEE Wireless and Microwave Technology Conference, WAMICON 2024, 2024)
In this article a novel concept of a dielectric chip-to-chip interconnect utilizing a dielectric image line is described. It is implemented by connecting two differential transmission lines, e.g. located at two ICs using an automated additive extrusion process to connect the two components. Therefore, transitions, i.e. wave mode transducers from the differential microstrip to the dielectric image line mode are developed. The 60mm long dielectric image line and two of the developed transducers show a deembedded insertion loss of around 4 dB from 100 to 110 GHz. This may point the way to novel interconnects for frequency ranges from a few hundred GHz to the THz range, where conventional stripline technology would be disadvantageous.
CRIS-Team Scopus Importer:2024-05-31
Keywords: additive manufacturing; chip to chip connection; dielectric image line; transition; wavemode transducer